The a^3 – b^3 formula is (a – b) (a^2 + ab + b^2). This formula is used to calculate the difference of two cubes.
What is a^3-b^3 Formula?
The a3-b3 formula is (a – b) (a2 + ab + b2)
Prove a Cube Minus b Cube Formula (a^3-b^3)
Let’s prove a cube minus b cube formula. To prove that a3 – b3 = (a – b) (a2 + ab + b2).
LHS = RHS
LHS = a3 – b3
On Solving RHS side we get,
= (a – b) (a2 + ab + b2)
On multiplying a and b separately with (a2 + ab + b2)
= a (a2 + ab + b2) – b(a2 + ab + b2)
= a3 + a2b + ab2 – a2b – ab2 – b3
= a3 + a2b – a2b + ab2– ab2 – b3
= a3 – 0 – 0 – b3
= a3 – b3
Hence proved, LHS = RHS
Prove that (a + b + c) ^ 3 – a ^ 3 – b ^ 3 – c ^ 3 = 3(a + b)(b + c)(c + a)using a^3-b^3 Formula?
To prove (a+b+c)^3 −a^3 −b^3 −c^3 =3(a+b)(b+c)(c+a) using the a^3 − b^3 formula, let’s first expand (a+b+c)^3 using the binomial theorem:
(a+b+c)3=(a+b+c)(a+b+c)(a+b+c)
Now, applying the distributive property and multiplying each term
(a+b+c)3=(a2+ab+ac+ab+b2+bc+ac+bc+c2)(a+b+c)
=(a2+2ab+2ac+b2+2bc+c2)(a+b+c)
=a3+a2b+a2c+2a2b+2ab2+2abc+2a2c+2abc+2bc2+ab2+b3+b2c+a2c+2abc+ac2+bc2+c3
=a3+b3+c3+3(a2b+a2c+ab2+abc+ac2+bc2)
Now, we subtract a^3 +b^3 +c^3 from both sides:
(a+b+c)3−a3−b3−c3=3(a2b+a2c+ab2+abc+ac2+bc2)
Divide both sides by 3:
(a+b+c)3−a3−b3−c3/3 =a2b+a2c+ab2+abc+ac2+bc2
a2b+a2c+ab2+abc+ac2+bc2=ab(a+b)+ac(a+c)+bc(b+c)
Now, the equation becomes:
(a+b+c)3−a3−b3−c3/3=ab(a+b)+ac(a+c)+bc(b+c)
Multiply both sides by 3:
(a+b+c)3−a3−b3−c3=3(ab(a+b)+ac(a+c)+bc(b+c))
3(ab(a+b)+ac(a+c)+bc(b+c))=3(a+b)(a+c)(b+c)
Thus, we have proven that:
(a+b+c)3−a3−b3−c3=3(a+b)(a+c)(b+c)
Examples on a^3-b^3 Formula
Here are a some examples on a3-b3.
Example 1: Find the Value of 833-533 Using the a^3-b^3 Formula.
Solution:
To find 833− 533 using the a3−b3 formula:
Let us assume that a = 83 and b = 53
Apply a3−b3 formula: a3 – b3 = (a – b) (a2 + ab + b2)
(83−53)(832+(83×53)+532)
=(83-53)(832+4399+532)
=(83-53)(6889+4399+2809)
=(30) (14097)
Now, multiply (a – b) by (a2 + ab + b2)
= 422910
Therefore, 833−533=422910
Example 2: Simplify 19^3-20^3 Using a Cube Minus b Cube Formula
Solution
To find 19^3 – 20^3
Let us assume a = 19 and b = 20
Using formula a3 – b3 = (a – b) (a2 + ab + b2)
a3 – b3 = (a – b) (a2 + ab + b2)
193 – 203 = (19 – 20) (192 + (19)(20) + 202)
= (-1) (361 + 380 + 400)
= (-1) (1141)
= -1141
Therefore, 19^3-20^3 = -1141
FAQ’s Related a^3-b^3 Formula
What is the Expansion of a3 – b3 Formula?
a3– b3 formula is read as a cube minus b cube. The a3– b3 expansion is expressed as (a – b) (a2 + ab + b2).
What is the Formula for a^3-b^3?
The formula for a^3 – b^3 is (a – b) (a^2 + ab + b^2)
What is a3 – b3 Formula in Algebra?
The formula for a3-b3 in algebra is a^3- b^3= (a – b) (a^2 + ab + b^2). This formula is used for factoring and simplifying the expressions involving the difference of two cubes.
What are a^3 – b^3 and a^3 + b^3 Formulas?
The formula of a3-b3 = (a – b) (a2 + ab + b2)
The formula for a3+b3 = (a + b)(a2 – ab + b2)
What is a Cube Minus b Cube Formula?
The formula of a Cube Minus b Cube is a3-b3 = (a – b) (a2 + ab + b2)